Histone Deacetylase Inhibitors: Synthesis of Tetrapeptide Analogue SAHA/TPX - Lynda Ekou; Tchirioua Ekou; Isabelle Opalinski; Jean Pierre Gesson (E-Journal of Chemistry)
The inhibition of HDAC (histone deacetylase) activity by specific inhibitors induces growth arrest, differentiation and apoptosis of transformed or several cancer cells. Some of these inhibitors are in clinical trial at phase I or phase II. The discovery and development of specific HDAC inhibitors are helpful for cancer therapy. In this paper we describe the synthesis of simple inhibitor B hybrid analogue suberoylanilide hydroxamic acid (SAHA), trapoxin B (TPX B) in as little as five steps. This compound is interesting lead for the design of potent inhibitors of histone deacetylase.